Melanoma Inhibitory Activity (MIA) increases the invasiveness of pancreatic cancer cells - El Fitori, Jamael (BioMed Central, 2005)
BACKGROUND: Melanoma inhibitory activity (MIA) is a small secreted protein that interacts with extracellular matrix proteins. Its over-expression promotes the metastatic behavior of malignant melanoma, thus making it a potential prognostic marker in this disease. In the present study, the expression and functional role of MIA was analyzed in pancreatic cancer by quantitative real-time PCR (QRT-PCR), immunohistochemistry, immunoblot analysis and ELISA. To determine the effects of MIA on tumor cell growth and invasion, MTT cell growth assays and modified Boyden chamber invasion assays were used. RESULTS: The mRNA expression of MIA was 42-fold increased in pancreatic cancers in comparison to normal pancreatic tissues (p < 0.01). In contrast, MIA serum levels were not significantly different between healthy donors and pancreatic cancer patients. In pancreatic tissues, MIA was predominantly localized in malignant cells and in tubular complexes of cancer specimens, whereas normal ductal cells, acinar cells and islets were devoid of MIA immunoreactivity. MIA significantly promoted the invasiveness of cultured pancreatic cancer cells without influencing cell proliferation. CONCLUSION: MIA is over-expressed in pancreatic cancer and has the potential of promoting the invasiveness of pancreatic cancer cells.